(untitled) (PRÁXIS EM SAÚDE, 2025)
This article aims to analyze the basic psychodiagnostic internship, an essential requirement in the Psychology program. The clinical practice was conducted at the Psychology School Service of URI – Santiago Campus, providing significant learning experiences regarding clinical practice and its importance for both academic training and the student’s personal development. The internship experience proves to be fundamental for integration into the clinical context and for the holistic growth of the future psychologist.